Impact of the revised starting lottery in the alpine speed events on performance of the top athletes - Kolbinger, O.; Kolbinger, E.; Beckmann, J.; Lames, M. (Current Issues in Sport Science, 2023)
Before the 2016/17 season, the International Ski Federation conducted major changes to its starting lottery, which defines the starting order in advance of each race of the speed disciplines. As part of this change, the top seeded athletes from then on were able to pick a starting position. Therefore, the aim of this study is two-folded. First, we explored the pick behavior of the top athletes and analyzed if they were able to identify favorable starting positions. Second, we investigated the influence of the rule change on competitive balance. Our sample consisted of 322 races with 17,725 individual performances of the seasons 2011/2012 to 2020/2021 and all our analysis were run separately for Women`s Downhill, Women`s Super G, Men`s Downhill and Men`s Super G. We could show that for all disciplines and both genders athletes heavily preferred to start around starting position 7. To start from such positions only led to significantly better rankings in Men`s Super G (z = 2.04, p = .041), but common language effect size showed the same trend for Women`s Super G (CL: 51.9%) as well as Men`s (CL: 53.3%) and Women`s Downhill (CL: 53.6%) competitions. In addition, male starters seeded among the top 7 performed significantly better after the rule change (Downhill: z = 2.95, p = .002; Super G: z = 2.89, p = .002), whereas they performed worse in Women`s Super G (z = -2.77, p = .005). Our findings indicate that there is a change in competitive balance for men`s competitions but not for women`s competitions. In addition, combining these findings with the detected picking preferences of the top athletes, we conclude our work with suggestions for further adaptions of the starting lottery.